2011
DOI: 10.1111/j.1743-6109.2010.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function After Rectocele Repair

Abstract: Introduction Pelvic organ prolapse is a common condition among women with a prevalence of 11% and may affect the anterior, posterior, or apical compartment with a negative impact on sexual function. Aim Aim of the current study was to evaluate sexual function before and after surgical rectocele fascial repair in sexually active patients who suffer from symptomatic rectoceles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Research so far shows miscellaneous results. Six studies support our finding [3,7,10,11,13,14], however, several studies found deterioration [8,[19][20][21][22]. The latter was particularly associated with implant surgery in the first three months postoperatively.…”
Section: Main Findingssupporting
confidence: 71%
See 1 more Smart Citation
“…Research so far shows miscellaneous results. Six studies support our finding [3,7,10,11,13,14], however, several studies found deterioration [8,[19][20][21][22]. The latter was particularly associated with implant surgery in the first three months postoperatively.…”
Section: Main Findingssupporting
confidence: 71%
“…Research on the influence of POP surgery on the sexual functioning shows conflicting results. Results range from improvement, [3,[7][8][9][10][11][12][13][14] to unchanged, [15][16][17] and deterioration of sexual functioning postoperatively [3,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…First, several prospective observational studies using the FSFI as measure for sexual function after nonmesh vaginal POP surgery found significant improvement in different domains [20,26–28]. One study described improvement on almost all domains, except for pain, which significantly deteriorated [26].…”
Section: Discussionmentioning
confidence: 99%
“…The recent study by Brandner et al. reported improvement in desire, pain, and satisfaction after rectocele repair [28]. Again a different population including only sexually active women with a partner, receiving both primary and secondary repair were included.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Brandner et al. prospectively evaluated sexual function in 68 women, 6 months following posterior repair using the FSFI questionnaire [17]. They showed significant improvement in desire, satisfaction, and pain but not in arousal, lubrication, and orgasm.…”
Section: Discussionmentioning
confidence: 99%